Court Auctions : Effective Processes and Enforcement Agents - Gramckow, Heike (World Bank, Washington, DC, 2014)
This paper considers the historical origins and efficacy of enforcement of civil court judgments, with a special focus on court auctions. It reviews the procedural and practical options available to courts and associated agencies for the identification of assets that may be used to satisfy a judgment debt and the processes for court-supervised asset seizure and sale by public auction. The efficiencies of public court auction processes are considered, including the elements of enforcement systems that can produce sub-optimal returns on sold assets and higher incentives for corrupt practices. Also considered is the trend in some systems for greater use of private agents as a means by which the cost of court enforcement processes can be reduced and for overcoming sometimes lengthy delays in enforcement. The paper concludes by identifying alternatives to public auction that in some cases can offer better prospects of assuring full payment of a judgment debt.